Metastatic castration-resistant prostate cancer: targeting the mechanisms of resistance to abiraterone acetate and enzalutamide. Issue 9 (September 2015) - Modena, Alessandra; Ciccarese, Chiara; Fantinel, Emanuela; Bimbatti, Davide; Tortora, Giampaolo; Massari, Francesco
<x xml:space="preserve">Abstract</x> Persistent androgen receptor (AR) axis is a functionally important pathway for prostate cancer cells and it is currently regarded as a critical therapeutic target. Although the impressive clinical activity of new hormonal agents, such as the second-generation AR antagonist enzalutamide (formerly MDV3100) and the selective inhibitor of cytochrome P450 17A1 (CYP17A1) abiraterone acetate (AA), in patients with metastatic castration-resistant prostate cancer (mCRPC), innate or acquired resistance invariably arises. To date, emerging hypotheses are different, but the mechanisms of resistance to these drugs have not yet been clarified. The aim of this review is to summarize the main data available on the evaluation of the multiple levels of development of resistance to next-generation AR-directed therapies. Understanding how the AR is activated may have clinical implications in defining which patients will respond to existing therapeutic agents and provide a proof for making novel strategies.